2016
DOI: 10.1136/annrheumdis-2016-210175
|View full text |Cite
|
Sign up to set email alerts
|

miR-10b-5p is a novel Th17 regulator present in Th17 cells from ankylosing spondylitis

Abstract: AS Th17 cells have a specific miR signature and upregulate miR-10b in vitro. Our data suggest that miR-10b is upregulated by proinflammatory cytokines and may act as a feedback loop to suppress IL-17A by targeting MAP3K7. miR-10b is a potential therapeutic candidate to suppress pathogenic Th17 cell function in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 16 publications
(9 reference statements)
1
49
0
Order By: Relevance
“…11 Currently, miRNAs have been speculated as therapeutic targets for improving AS treatment due to its aberrant expression in the T helper 17 cells from AS patients. 22 Meanwhile, the involvement of miRNAs as mediators has been implicated in various biological processes linked to the osteoblasts, such as apoptosis, metabolism, differentiation, proliferation, and bone formation, which provide a theoretical reference for targeting miRNAs in treating metabolic bone diseases. 23 Therefore, our study investigated the role of miR-96 in osteoblast differentiation and bone formation of AS.…”
Section: Discussionmentioning
confidence: 99%
“…11 Currently, miRNAs have been speculated as therapeutic targets for improving AS treatment due to its aberrant expression in the T helper 17 cells from AS patients. 22 Meanwhile, the involvement of miRNAs as mediators has been implicated in various biological processes linked to the osteoblasts, such as apoptosis, metabolism, differentiation, proliferation, and bone formation, which provide a theoretical reference for targeting miRNAs in treating metabolic bone diseases. 23 Therefore, our study investigated the role of miR-96 in osteoblast differentiation and bone formation of AS.…”
Section: Discussionmentioning
confidence: 99%
“…IL-21 participates in HIV-1 control in vivo via inducing microRNA-29 (miR-29) [30]. And IL-17A would be suppressed by miR-10b to participate the pathological processes of ankylosing spondylitis [31]. Moreover, IL-34 modulates HCC metastasis through microRNA-28 [32].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from let‐7i and miR‐130a, a recent study reported that AS Th17 cells increased expression of the miR‐10b‐5p, miR‐155‐5p, and miR‐210‐3p. Chen et al () further described the function of one of these, miR‐10b, in the regulation of cytokine production by Th17 cells. IL‐6 and TNF‐α increased expression of the miR‐10b, which in turn inhibited IL‐17A production.…”
Section: Biogenesis Of Mirnasmentioning
confidence: 99%